(untitled) (Південний архів (історичні науки), 2021)
The paper analyzes the effect of special, additional and individual legislative acts adopted by the central authorities in order to supplement and specify the positions of the Charter of 1785 to improve the financial state of the towns and cities in the Southern Ukrainian region. The role of the regional-individual laws for the towns and cities in the South of Ukraine was extremely important since they offered opportunities for the development of the municipal budgets and trade. Excise duties, farming of revenues and servitude were common for all the provinces in the South of Ukraine. They differed in private privileges, for instance, class payments were more characteristic of the towns in Ekaterinoslav province, more privileges were given on trade and land ownership for the towns of Taurida province. The only province in the South of Ukraine, the towns of which were given some financial assistance, was Kherson province. Financial support was given to the towns from the state treasury for the best payment of the state taxes. But the only conclusion that can be drawn is that the towns and cities in the South of Ukraine did not have a satisfactory financial position. According to new laws, many positive phenomena were introduced, but the financial position of the towns and cities did not improve. For instance, the self-government had more opportunities and rights in managing the municipal economy and more independence in the formation and use of the budget. But the general plan of dividing estimates into mandatory and non-mandatory costs, direct and indirect, current and occasional profits, direct and indirect, ordinary and extraordinary remained without changes. The conclusions emphasize that, as a result of the effect of additional, special and individual laws, the newlyestablished municipal public authorities in the South of Ukraine received mandatory costs for the state needs with much less opportunities in financial and economic initiative. Therefore, the social-economic activity was enclosed in the space of legislative-administrative directives, but the activity of individual municipalities had their own specificity of the development.